The first four years - Wilder, Laura (Ingalls) 1867-1957.; Williams, Garth (New York : Harper & Row, 2007)
During their first four years of marriage, Laura and Almanzo Wilder have a child and fight a losing battle in their attempts to succeed at farming on the South Dakota prairie.
G9
Keywords: Wilder, Laura Ingalls, -- 1867-1957 -- Juvenile fiction; Wilder, Almanzo -- Juvenile fiction; Wilder, Laura Ingalls, -- 1867-1957 -- Fiction; Wilder, Almanzo -- Fiction; Frontier and pioneer life -- Fiction; South Dakota -- Fiction